Futbolda Hakem Hatası ve Kural Hatası - Balcı, Murat; Turan, Sinem (Türkiye Barolar Birliği, 2023)
Bu çalışmada öncelikle hakemin yanlış bir kanaat kullanmak suretiyle vermiş olduğu kararlar ile bir kuralın uygulanmaması veya yanlış uygulanması durumunda vermiş olduğu kararların nitelendirilmesi yapılarak hakem hatası ve kural hatası kavramları açıklanacak, akabinde bu iki kavramın hukuki sonuçları ele alınarak, örnek olarak ulusal ve uluslararası otoritelerin bu konuda vermiş olduğu kararlar incelenecektir.

In this study, the decisions made by the referee using a wrong opinion and the decisions made in case a rule is not applied or applied incorrectly will be described and the concepts of referee error and violation of rule will be explained first. The legal consequences of these two concepts will be discussed and the decisions made by national and international authorities on this matter will be examined.
Referee’s Error and Violation of A Rule in Football
Keywords: Futbol; Hakem Hatası; Kural Hatası; Tahkim Kurulu; Football; Referee’s Error; Violation of a Rule; Arbitration Board